America and the Holocaust : A Documentary History - Medoff, Rafael, 1959- (Book collections on Project MUSE., 2022)
"The first comprehensive volume to teach about America's response to the Holocaust through visual media, America and the Holocaust: A Documentary History explores the complex subject through the lens of 100 important documents that help illuminate and amplify key episodes and issues"--